Hydrodynamic forces on a partially submerged cylinder at high Reynolds number in a steady flow. (July 2019) - Ren, Haojie; Xu, Yuwang; Zhang, Mengmeng; Deng, Shi; Li, Shuai; Fu, Shixiao; Sun, Hao
Highlights: Significant mean downward lift forces in the CF direction caused by the free surface effects are first observed. An empirical formula for predicting whether "overtopping" occurs is proposed based on the experimental results. Two distinct features of the mean hydrodynamic coefficients in the non-overtopping and overtopping regions are observed. Abstract: The hydrodynamic forces on the stationary partially submerged cylinder are investigated through towing test with Reynolds number ranging from 5 × 10 4 to 9 × 10 5 . Three test groups of partially submerged cylinders with submerged depths of 0.25 D, 0.50 D, and 0.75 D and one validation group of fully submerged cylinders are conducted. During the experiments, the hydrodynamic forces on the cylinders are measured using force sensors. The test results show a considerable difference in the hydrodynamic coefficients for the partially submerged cylinders versus the fully submerged cylinders. A significant mean downward lift force is first observed for the partially submerged cylinders in a steady flow. The maximum of the mean lift coefficients can reach 1.5. Two distinct features are observed due to the effects of overtopping: random distributions in the mean drag coefficients and a clear quadratic relationship between the mean lift coefficients and the Froude number appear in the non-overtopping region. However, the novel phenomenon of a good linear relationship with the Froude number for the mean hydrodynamic coefficients is clearly shown in the overtopping region. In addition, fluctuating hydrodynamic coefficients are further proposed and investigated. These results are helpful to have a better understanding of the problem and to improve related structural designs.